Logic, language, and computation : 11th International Tbilisi Symposium on Logic, Language, and Computation, TbiLLC 2015, Tbilisi, Georgia, September 21-26, 2015, Revised selected papers /: 11th International Tbilisi Symposium on Logic, Language, and Computation, TbiLLC 2015, Tbilisi, Georgia, September 21-26, 2015, Revised selected papers. (2017) - Unknown
No abstract available